Spread Of Laterite Nickel Based on Drill Data at PT Manunggal Sarana Surya Pratama, Southeast Sulawesi Province - Aswadi, Muhammad; Rauf Husain, Jamal; Gazali, Ahmad; Budiman Thamsi, Alam (Journal of Geology and Exploration, 2022)
Modeling of nickel laterite resources is intended to determine the distribution of resources represented in the form of block models. The results of resource modeling indicate the shape and distribution of mineral deposits which can facilitate the mining process and can predict mining boundaries referring to the results of resource modeling. The purpose of this study was to determine the thickness of the saprolite zone layer and the distribution direction of nickel laterite based on drill point data. The data used in the laterite nickel resource modeling are exploration drill data, drill coordinates, and exploration grade classification. Data processing and analysis methods apply block modeling and the variogram method to determine the distribution direction of nickel resources. Based on the results of the cross-section profiles in Section 1 to Section 7, the average thickness of saprolite is 6,605 m, and the block model layer of saprolite which shows high levels of red color (Ni 1.9 - so on) is the most in the north, pink color (Ni 1.5-1.89) is in the north direction before the Ni 1.9 level above, the green color (Ni 1.3-1.49) is in the east and south.